Proto-Baltic? - Kortlandt, Frederik (Baltistica, 2018)
There is little or no evidence for a period of common West and East Baltic innovations after the period of common Balto-Slavic developments before the separation of Slavic from the Baltic languages. The terms “Proto-Baltic” and “Proto-Balto-Slavic” refer to the same thing, and Slavic may alternatively be called “South Baltic”. The opposite view is taken by Miguel Villanueva Svensson (2014) and Eugen Hill (2016). Here I specify the differences which underlie the disagreement.